Job agent management system - Chun Ling, Lu (2012)
Job Agent Management System(JAMS)is an online based management system for job agent company,Epromode Sdn Bhd. Data in the system can be accessed through web browser in the market or Android application that specially developed for JAMS.It is a software solution to solve the problem of project management as well as human resource management in Epromode Sdn Bhd.The main problem faced by Epromode Sdn Bhd is the speed and efficiency of main branch to update project status in different branches,especially promoter hired status for each project.Besides that,it is too much paper work in the current manual system that increases the cost of material resources as well as cost of human resources if too much overtime working hours by staff.The objectives are to create JAMS are to develop a computerized and efficient management system to replace their current system. Besides that,it is used to keep information of projects and human resources of Epromode Sdn Bhd in a more manageable way, in order to reduce problems that might occur from human error when done manually. JAMS have four types of user, which are administrator, supervisor, promoter, and applicant. All the information is stored in database and can be accessed by using web browser or Android application through internet connection.The Android application in JAMS is specially developed for supervisors in Epromode Sdn Bhd who needs to outstation. When a supervisor is outstation, Android application provides a fast access way instead of using web browser in the phone.